Background‐Free Proton NMR Spectroscopy with Radiofrequency Amplification by Stimulated Emission Radiation. Issue 50 (1st October 2021) - Joalland, Baptiste; Theis, Thomas; Appelt, Stephan; Chekmenev, Eduard Y.
Abstract: We report on the utility of Radiofrequency Amplification by Stimulated Emission Radiation (RASER) for background‐free proton detection of hyperpolarized biomolecules. We performed hyperpolarization of ≈0.3 M ethyl acetate via pairwise parahydrogen addition to vinyl acetate. A proton NMR signal with signal‐to‐noise ratio exceeding 100 000 was detected without radio‐frequency excitation at the clinically relevant magnetic field of 1.4 T using a standard (non‐cryogenic) inductive detector with quality factor of Q =68. No proton background signal was observed from protonated solvent (methanol) or other added co‐solvents such as ethanol, water or bovine serum. Moreover, we demonstrate RASER detection without radio‐frequency excitation of a bolus of hyperpolarized contrast agent in biological fluid. Completely background‐free proton detection of hyperpolarized contrast agents in biological media paves the way to new applications in the areas of high‐resolution NMR spectroscopy and in vivo spectroscopy and imaging. Abstract : Radiofrequency Amplification by Stimulated Emission Radiation (RASER) was employed for background‐free detection of hyperpolarized NMR resonances even in the extreme case of protonated solvents and biological fluids. This approach paves the way to a wide range of high‐resolution NMR‐ and in vivo MRI applications of proton detection of hyperpolarized molecules.